PROGRAM PEMBIASAAN HARIAN DALAM MEMBENTUK KARAKTER SISWA DITINJAU DARI PERSPEKTIF PSIKOLOGI BELAJAR - Lia Dwi Tresnani; Muhammad Khoiruzzadi (stit-islamic-village, 2020)
This study aims to determine the program of daily habituation activities in shaping the character of students of SMP Negeri 6 Pekalongan City, looking for what characters are to be formed in each daily habituation activity program, and concepts in psychological learning theory in explaining the process of habituation activities in shaping student character. This research is included in the field research with a descriptive qualitative approach. The results of the study of daily habituation programs in SMP Negeri 6 Pekalongan City are scheduled and conditional, namely tadarus and prayers before KBM (religious and disciplinary), duha prayer (religious and responsibility), dzhuhur prayers (religious and responsibility), canteen honesty (honesty), orderly coming and going home (discipline and responsibility), orderly appearance (discipline and responsibility), respectful flags singing the national anthem, and folk songs (love of the motherland and national spirit), group class picket (care about the environment and responsibility), conditioning the cleanliness (care for the environment), separation of organic and non-organic waste (care for the environment and responsibility). From the daily habituation program can be explained psychological approach, especially with learning theories, including (1) changes in student behavior with habituation activities and carried out repeatedly will be a reinforcer in student behavior in addition to reward and punishment as a reminder process for students, (2 ) students' self-awareness in behaving because of changes in student behavior needs to be seen from the cognitive development of students. Some students are still in the level of concrete operations and most have entered the formal operational stage so students are able to think more mature and able to think logically and logically. In addition, changes in student behavior are formed due to the process of imitation and demonstration from teachers in particular, and friends at school in general. So the role of the teacher, the school environment and the cognitive abilities of students is an important key in shaping behavior.